Mechanical properties of the GX12CrMoVNbN91 (GP91) cast steel after different heat treatments - Golański, G. (Фізико-хімічна механіка матеріалів, 2012)
The paper presents results of research on the influence of multistage heat treatment of different types on the microstructure and properties of high-chromium martensitic GX12CrMoVNbN9-1 (GP91) steel. The material under investigation were samples taken out from a test coupon. Heat treatment of GP91 cast steel was performed at the parameters of temperature and time typical of treatment for multi-ton steel casts. The research has proved that in the as-cast state the GP91 cast steel was characterized by a coarse grain microstructure of lath martensite with precipitations of carbides such as: M₂₃C₆, M3C and NbC. The cast steel microstructure in the as-cast state ensured the required standard mechanical properties. Heat treatment of GP91 cast steel contributed to the obtainment of a fine grain microstructure of high tempered lath martensite with numerous precipitations of M₂₃C₆ and MX carbides of diverse size. The GP91 cast steel structure received by heat treatment made it possible to obtain high plastic properties, mainly impact strength, maintaining strength properties (yield strength (YS)) on the level of the required minimum. Представлено результаты исследований влияния различного вида многоэтапной термообработки на микроструктуру и свойства высокохромовой мартенситной литой стали GX12CrMoVNbN9-1 (GP91). Для исследований взято образцы, получённые из пробного слитка. Термообработку литой стали GP91 осуществляли в температурновременных параметрах, соответствующих обработке многотонного литья стали. Исследования показали, что в литом состоянии сталь GP91 имеет крупнозернистую микроструктуру пластинчатого мартенсита с содержанием карбидов типа M₂₃C₆, M3C и NbC, которая соответствует требуемым механическим свойствам по стандарту. С помощью термообработки литой стали GP91 получено мелкозернистую микроструктуру высокоотпущенного пластинчатого мартенсита с многочисленными вкраплениями типа M₂₃C₆ и МX различного размера. Структура литой стали GP91 после термообработки получила высокие пластические характеристики, преимущественно упругости, со свойствами прочности (границы пластичности) приближенные к требуемому минимуму. Подано результати досліджень впливу різного виду багатоетапної термо- обробки на мікроструктуру і властивості високохромової мартенситної литої сталі GX12CrMoVNbN9-1 (GP91). Для досліджень взято зразки, отримані з пробного злитка. Термообробку литої сталі GP91 здійснювали в температурно-часових параметрах, характерних для обробки багатотонного лиття сталі. Дослідження показали, що в литому стані сталь GP91 має грубозернисту мікроструктуру пластинчастого мартенситу із вмістом карбідів типу M₂₃C₆, M3C і NbC, яка відповідає механічним властивостям за стандартом. За допомогою термообробки литої сталі GP91 отримано дрібнозернисту мікроструктуру високовідпущеного пластинчастого мартенситу з чисельними вкрапленнями типу M₂₃C₆ і МX різного розміру. Структура литої сталі GP91 після термообробки одержала високі пластичні характеристики, переважно пружності, з властивостями міцності (межі пластичності) наближені до необхідного мінімуму.